Modelagem computacional de incêndios e queimadas : um estudo de caso sobre a Reserva Biológica do Lago Piratuba-AP - Silva Júnior, Dinaldo Barbosa da (2007)
Motivated by urgent necessity to support the studies of strategies, controlling and combat to big fires, mainly in forest reserves, we develop a computational tool for assistance in this task. Our main goal in this work was to elaborate software, and to develop a first case study, that is fire simulation in the REBIO of the Lake Piratuba AP. We reached this goal in three stages: first, we created a logical and mathematical model about tree combustion dynamics of reactions and the thermodynamics; second, we implement a computational program in a professional language for becomes it accessible or portable; third, we carry through a test with actual images of satellite of the REBIO of the Piratuba Lake. We got fire images simulated in virtual forests that demonstrated a high degree of realism or similarity that it is observed in real images. We also applied this software in satellite images of REBIO. The results of the dynamic images demonstrate the expected qualitative effect, but the geometric delimitation of the reached areas is more evident with the precise fire extension visualization, in the map scale, and its consequences, allowing that space and time, useful parameters to the fireman service, are measured in the simulation.